2015
DOI: 10.1016/j.jspd.2014.06.008
|View full text |Cite|
|
Sign up to set email alerts
|

Incidence and Risk Factors for Major Surgical Complications in Patients With Complex Spinal Deformity: A Report From an SRS GOP Site

Abstract: Postoperative complications were seen in 20% of surgically treated patients with complex spine deformities at a Scoliosis Research Society SRS Global Outreach Program site. Three-column osteotomies were identified as an independent risk factor of both postoperative complications and neurological deficits. The significant observed correlation of 3-column osteotomies and postoperative neurological deficits should serve as a guide for surgeons in the preoperative planning and management of severe spinal deformiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 16 publications
1
41
0
Order By: Relevance
“…The reported rate of postoperative neurologic decline after complex ASD surgery in the Scoli-RISK-1 study was higher than that reported in most of the existing literature [5][6][7][8][9][10][11][12][13][14]16,17]. The Scoliosis Research Society Morbidity and Mortality Committee reported that new neurologic deficits after spine surgery, in general, were documented in 1,064 cases (1.0%) in their largest review of 108,419 spinal procedures [22].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The reported rate of postoperative neurologic decline after complex ASD surgery in the Scoli-RISK-1 study was higher than that reported in most of the existing literature [5][6][7][8][9][10][11][12][13][14]16,17]. The Scoliosis Research Society Morbidity and Mortality Committee reported that new neurologic deficits after spine surgery, in general, were documented in 1,064 cases (1.0%) in their largest review of 108,419 spinal procedures [22].…”
Section: Discussionmentioning
confidence: 94%
“…Given the numbers of these events encountered in our cohort, a decision was made to first select 10 variables as candidates to avoid overfitting of the final model [21]. Based on clinical relevance and knowledge from the existing literature, the following 10 variables were chosen: age, previous history of spine surgeries, preoperative neurologic deficits, coronal DAR, sagittal DAR, surgical approach (combined anterior and posterior approach vs. posterior-only approach), numbers of spinal levels involved, lumbar-level osteotomy, 3CO, and estimated blood loss [6][7][8][9][10][11][12][13][14][15][16][17]. Results of univariable analyses are summarized in Table 4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[4] Failure to treat the spinal tuberculosis could result in severe deformity of the spine, impairment of spinal cord, and failure of respiratory function. [5,6] Although it was once acceptable for patients to live with kyphotic deformity, now most patients hope to achieve close to normal spinal posture with the least invasive treatment method possible. [7] …”
Section: Discussionmentioning
confidence: 99%